Elementary Education in Jharkhand Progress and Policy Perspectives - Padhi, Sambit Kumar; Mahato, Haripad Kumar (JOURNAL OF INDIAN EDUCATION, 2022)
Universal elementary education has been at the centre of attention and accepted as a national goal in India since independence. In recent years, momentum has gathered throughout the country for the promotion of literacy, expansion in number of schools, school enrolment, etc. In order to achieve this goal, several programmes have been implemented both at the central and state levels over the years. However, in spite of all these initiatives, many students between the ages of 6–14 are not yet enrolled in the schools. The challenge for universalisation of elementary education is most severe in the educationally backward and newly formed states like Jharkhand. This paperis based on the study of progress occurred and policies implemented in the state of Jharkhand to attain the goal of elementary education. The paper analyses data pertaining to the growth or decline of elementary schools, enrolment of boys and girls, gross enrolment ratio, drop-out rates at various levels, teacher-pupil ratio in the state of Jharkhand from 2015–16 to 2019–20. The paper also makes an attempt to explore the measures taken by the state and central government for quality improvement of elementary education in the state of Jharkhand.